2011
DOI: 10.1093/cid/cir525
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Subclinical Avian Influenza Virus Infections Among Rural Thai Villagers

Abstract: These data suggest that people in rural central Thailand may have experienced subclinical avian influenza infections as a result of yet unidentified environmental exposures. Lack of an indoor water source may play a role in transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…To date, fewer than 20 human infections with H9N2 viruses have been reported; they all occurred in China or the Hong Kong Special Administrative Region. However, seroepidemiological studies suggest a larger number of human infections with H9N2 viruses (74)(75)(76). In addition, avian H9N2 influenza viruses have infected pigs on several occasions (77)(78)(79)(80), can replicate in experimentally infected dogs (81), and may acquire the ability to be transmitted between ferrets via respiratory droplets (82).…”
Section: Figmentioning
confidence: 99%
“…To date, fewer than 20 human infections with H9N2 viruses have been reported; they all occurred in China or the Hong Kong Special Administrative Region. However, seroepidemiological studies suggest a larger number of human infections with H9N2 viruses (74)(75)(76). In addition, avian H9N2 influenza viruses have infected pigs on several occasions (77)(78)(79)(80), can replicate in experimentally infected dogs (81), and may acquire the ability to be transmitted between ferrets via respiratory droplets (82).…”
Section: Figmentioning
confidence: 99%
“…10 In some studies, there seemed to be an association between seropositivity and exposure to untreated water, which may reflect the fact that H5N1 has been found in bodies of water contaminated by infected ducks. 9,16 Two recent studies among the 18 non-clade 0 studies reported higher rates of asymptomatic H5N1 exposure than others: one among inhabitants of rural Thai villages where H5N1 was endemic, where 5.6% were found to be seropositive; and another in Vietnam that reported 5% of a high-risk cohort were seropositive. 10,16 In the Thai study, seropositivity was associated with lack of indoor waterbut not poultry contact-suggesting the possibility of a water-related route of exposure.…”
Section: Seroepidemiologic Studiesmentioning
confidence: 98%
“…In the absence of confirmed clinical disease, a recent immunological surveillance of rural Thai villagers suggested that 9.1% of the serum samples contained antibodies against one of two H5N1 virus types suggesting subclinical prevalence. 33 Although the clinical severity of H5N1 viral infections in human can be disputed due to limited surveillance data, it is very important to be prepared against a pandemic outbreak of H5N1 influenza virus infections due to the naiveté of the human population to H5 antigens.…”
Section: Influenza Virus and Pathologymentioning
confidence: 99%